The Effectiveness of Deactivation Group Counseling Mode to Reduce Students’ Body Dissatisfaction - Nuraeni, Nisrina; Barida, Muya (citeus, 2025)
This research was motivated by students who exhibited high levels of body dissatisfaction. Body dissatisfaction can be defined as an individual's negative perception of their own body shape and physical condition, which may be influenced by discrepancies between their actual body standards and their desired body. This study assesses the efficacy of a deactivation group counseling approach in reducing body dissatisfaction among students at State Vocational School 4 Yogyakarta, Indonesia. The research adopted an experiment design using the pretest-posttest control group design model. The subjects were selected using simple random sampling. The subjects of this study were 10 students from tenth grade culinary 1, 2, and 3 at State Vocational School 4 Yogyakarta. The data collected in quantitative form (numbers) was then analyzed statistically. The statistical data analysis employed in this study was an independent sample t-test via SPSS 22. The findings revealed a notable decline in body dissatisfaction among the tenth grade Culinary students at State Vocational School 4 Yogyakarta. This was demonstrated by the mean pretest-posttest score on the body dissatisfaction scale, which decreased from 69.6 to 53.6 for the experimental group and from 71.8 to 66.2 for the control group after the deactivation group counseling mode was administered to the experimental group. Furthermore, the results of the independent sample t-test yielded a significant value of 0.028, indicating a p-value of less than 0.05. This suggests notable differences in the students' responses before and after the implementation of the deactivation group counseling mode. These findings substantiate the effectiveness of the deactivation group counseling mode in reducing body dissatisfaction among tenth grade culinary students at State Vocational School 4 Yogyakarta.